In situ TEM observations of high-strain-rate deformation and fracture in pure copper. (March 2020) - Voisin, T.; Grapes, M.D.; Li, T.T.; Santala, M.K.; Zhang, Y.; Ligda, J.P.; Lorenzo, N.J.; Schuster, B.E.; Campbell, G.H.; Weihs, T.P.
Graphical abstract: Abstract: The plastic deformation of polycrystalline metals at high strain rates is controlled by the way defects (dislocations and twins) nucleate, propagate, and interact in the microstructure. To-date, the role of these defects has been estimated based on dynamic mechanical measurements coupled with ex situ investigations of the deformed microstructure. However, such investigations are fundamentally limited in their ability to characterize transient mechanisms. Here, we present for the first time direct, experimental observations of the nucleation, motion, and interaction of defects and cracks during deformation of pure copper at strain rates between 10 3 and 10 4 s −1 . These observations are enabled by coupling a custom-built in situ high-rate straining stage with nanosecond-resolution dynamic transmission electron microscopy. The results show that while twins play only a minor role in the deformation of copper at quasi-static strain rates, the twin nucleation rate increases markedly at high strain rates. The preferred nucleation sites for twins also change, and the new twin interfaces become preferential paths for crack propagation, facilitating fracture through the original grains.